A rede social do homem com câncer na perspectiva bioecológica: contribuições para a enfermagem - Feijó, Aline Machado (2010)
The man who experiences the cancer, chronicle disease considered by society as fatal and stigmatized, needs more effectively of his social network, which serves as a support to live this situation in a safer manner. This way, it is considered of extreme relevance knowing the social network of the man when he gets sick, in other words, which supporting relations and bonds in this situation. It is also important the health professionals, specially the nurses, in the moment they identify this network try to reinforce the bonds that are intense and healthy and propose to the clients to plan in group ways of improving or modify the fragilized and stressed bonds. The study had as an objective to know the social network of the man with cancer in chemotherapeutic treatment, in the bioecological perspective. It consists in a qualitative study which used as a theoretical referential the bioecological model by Urie Bronfenbrenner and the method of Ecological insertion. It was developed with three man with cancer attended in the service of chemotherapy of the Hospital Escola da Universidade Federal de Pelotas, in the period of April to September of 2010, realizing in average six meeting with each one of the subjects. The first approach to the subjects was realized in this service when they were invited to participate of the study, and after that the meetings were realized in the house of each one with a early schedule. The data collection occurred through a semistructured interview and ecomap, with record in field diary. The data were submitted to thematic analyses. It was certified that the strengthening of the relations and development of the man with cancer are necessary positive characteristics in his social network, like: presence, communication, sharing, trust, respect, appreciation, reception, interest, help and protection. These are ways of matured support overtime which influenced in the life of the people in a healthy way. It is essential for his reorganization in the process of sickening. It is necessary emphasize the nurse may become a supporting bond, because it s the health professional who should be closer to the client and, this way, could have more easiness to communicate and get the necessities of the sick person, and even become the link between the person/family (microsystem) and the other systems. Besides, knowing the social network of these people is essential to intervene in a positive way in their relations. So, it is intended with this research extend the knowledge of the health professionals and stimulate the production of more investigations focused in this area, in order to deepen the knowledge about the social network of the man with cancer, emphasizing the importance of the supporting bonds in this condition.